Surgical treatment of children with drug‐resistant epilepsy involving the Rolandic area. Issue 2 (15th June 2021) - Wang, Shuang; Zhang, Hongwei; Liu, Chang; Liu, Qingzhu; Ji, Taoyun; Wang, Wen; Yu, Guojing; Cai, Lixin; Liu, Xiaoyan
Abstract: Objective . We retrospectively analysed the clinical features and prognostic factors of surgery in children with drug‐resistant epilepsy involving the Rolandic area, and the relationship between the stable compound muscle action potentials (CMAPs) of intraoperative neurophysiological monitoring (IONM) and good motor function outcomes postoperatively. Methods . A study was conducted on the clinical data of 91 patients with epilepsy who underwent epilepsy surgery involving the Rolandic area and IONM from November 2015 to February 2019. Results . In total, 91 patients were included in this study. The median age at seizure onset was 1.3 years old. The median age at surgery was 4.4 years old. Twenty‐seven patients (29.7%), with age at onset below three years old, had epileptic spasms. The central operculum was the most common surgical region in 52 patients (57.1%). The most common pathology was focal cortical dysplasia (FCD) in 67 patients. At the last follow‐up visit, 69 patients (75.8%) were seizure‐free. Interictal epileptiform discharges in the Rolandic area were associated with good seizure outcome ( p =0.016). Out of 91 patients, successful IONM was performed in 88 patients (96.7%). Stable CMAP was seen in 79 of 88 patients (89.8%), and irreversible disappearance of CMAP was seen in nine patients (10.2%). New permanent motor deficit was observed in 13 of 88 patients (14.8%). There was a significant correlation between stable CMAP and good motor function outcome ( p <0.001). Significance . This is the largest reported cohort of children with drug‐resistant epilepsy involving the Rolandic area who received surgery from a single centre. Epileptic spasms were only observed in young children with age at onset below three years old. The major aetiology was FCD. The rate of seizure freedom was 75.8%. Epileptiform discharges in the Rolandic area were the main prognostic factor affecting surgical outcome. Stable CMAP can predict good motor function outcome postoperatively.